Developing Air Defense Strategies Using Data Mining Techniques - ابو قاسم, كندة; عيسى, يامن; محرز, علاء (Latakia University Journal -Engineering Sciences Series, 2021)
This paper discusses the development of air defense strategies by gathering information on battalions' action that communicates with the Headquarter and that is by designing a decision support system that processes the real-time information received by the Headquarter this is to help the leader in making the right decision, which needs accuracy, speed and complex calculations. The radar center was relied upon as a source for air target information (Warplanes – missiles) the study was conducted for three different types of air defense battalions. The system displays the results on the commander's screen, which includes the decision to select the appropriate battalion to deal with the air target and all information related to the combat work as it is stored in a database. After the data collection process we designed a knowledge discovery model using data mining by applying the k-means cluster algorithm to the generated dataset ,Where several experiments were performed with different values of k in order to reach the lowest square error and a sufficient number of clusters so that we were able to obtain useful information. The results of the cluster trials showed the effectiveness of the battalions, these results help the commanders to take measures that increase the effectiveness of the battalions and to develop an air defense works strategy.